2011
DOI: 10.3109/14767058.2011.636463
|View full text |Cite
|
Sign up to set email alerts
|

Maternal red blood cell folate concentration at 10–12 weeks gestation and pregnancy outcome

Abstract: Maternal RBC folate concentration in early pregnancy is associated with SGA and PTB, but not with preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 21 publications
3
40
1
Order By: Relevance
“…Our findings that moderate folate levels in early pregnancy are associated with higher birth weight regardless of race/ethnicity are consistent with previous studies, [14][15][16][17][18][19][20][21][22][23][24]50 although an equally large number of studies from Europe, Asia and the US [25][26][27][28][29][30][31] have not confirmed these associations. Reasons for discordant findings are unclear.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings that moderate folate levels in early pregnancy are associated with higher birth weight regardless of race/ethnicity are consistent with previous studies, [14][15][16][17][18][19][20][21][22][23][24]50 although an equally large number of studies from Europe, Asia and the US [25][26][27][28][29][30][31] have not confirmed these associations. Reasons for discordant findings are unclear.…”
Section: Discussionsupporting
confidence: 80%
“…13 In humans, evidence of associations between maternal folate concentrations and fetal growth is conflicting, as high levels have been linked to both low and high birth weight, [14][15][16][17][18][19][20][21][22][23][24] while other studies found no associations. [25][26][27][28][29][30][31] Extremes of the birth weight distribution have been associated with a wide range of childhood and adultonset chronic diseases and conditions including obesity, impaired glucose tolerance, type 2 diabetes, coronary artery disease, congestive heart failure and some cancers.…”
Section: Introductionmentioning
confidence: 86%
“…While most of the studies finding an association with gestational length or PTD were based on high doses of folic acid (≥5000 μg/d [20,22,46], ≥2500 μg/d [22,47] and ≥500 μg/d [48-50]), only 2 women in our study population consumed as much as 5000 μg/d of supplemental folic acid, while only 10% consumed >500 μg/d and 16% consumed >400 μg/d. However, the Hungarian RCT, one of the biggest performed so far, did not find any effect of a high dosage of 800 μg/d of periconceptional folic acid supplementation on PTD [6].…”
Section: Discussionmentioning
confidence: 99%
“…In some countries like Greece and Norway, commonly used supplements contain folic acid and/or iron only [20]. In other countries, folic acid is mainly consumed in the form of multivitamins, making it difficult to differentiate the effects of multivitamin use and folic acid supplementation [21,37,43,50]. Vitamins other than folic acid might explain the association between multivitamin use and PTD.…”
Section: Discussionmentioning
confidence: 99%
“…There is some support from observational studies and trials that periconceptional supplementation with folic acid may improve fetal growth and birth weight (Rolschau et al , 1999; Relton et al , 2005; Timmermans et al , 2009; Furness et al , 2012), but the evidence remains controversial. A recent meta‐analysis of randomised controlled trials (Lassi et al , 2013) found no conclusive evidence of benefit of antenatal supplementation with folic acid on preterm birth, stillbirth, neonatal death, mean or low birthweight, mean or low pre‐delivery haemoglobin concentration, or pre‐delivery folate concentrations in serum or erythrocytes.…”
Section: Evidence Of Folate Deficiencymentioning
confidence: 99%